Kangaroo Mother Care: A Qualitative Study on the Practice and Experiences of Mothers of Preterm Neonates in a Tertiary Teaching Hospital in Eastern Uganda - Nteziyaremye, Julius; Nekaka, Rebecca; Naloli, Mercy; Ssenyonga, Lydia V. N.; Kagoya, Enid Kawala (International Journal For Research In Health Sciences And Nursing, 2021)
Introduction:Globally, neonatal deaths continues to be a challenge especially to to attainment of sustainable development goal 3 .About 4 million neonatal deaths per year,with 99% of the deaths occurring in low and middle resource countries,75% of these occurring in the first week of life.Prematurity remains an indirect leading cause of mortality and morbidity.Uganda’s progress on the improvement of perinatal morbidity and mortality has largely stagnated at 27 deaths per 1,000 live births from the year 2006. One of the cost-effective readily available interventions that would curtail perinatal mortality is kangaroo mother care(KMC)- a low tech four decades old intervention.However challenges about its implementation persist on in Uganda despite intensified implementation and roll-out startegies in 2010.This study,the first of its kind to the best of our knowledge in eastern Uganda sought to find the facilitators and barriers of KMC. Materials and methods:This was a qualitative study using in-depth interviews(IDI) carried out at a tertiary university teaching hospital.Twenty IDIs were carried out among mothers/caretakers using the phenomena theory.After each IDI, each transcript was analyzed by two researchers working independently using NVIVO software version 11 plus (QSR International, Burlington, Massachusetts) and themes and subthemes developed. Results:Majority of mothers/caretakers, were adolescents and young adults and primiparous at 55%.The major facilitators to KMC were supportive staff that facilitated positive attitude ,ability to substitute provider and family support.The major barriers were lack of family support,lack of male involvement,maternal stress and poor health and multiple gender roles, infrastructural challenges,and misconceptions associated with preterm births such as early sexual intercourse and lack of herbal medicine use. Conclusion:More facility leadership involvement and engagement of mothers during antenatal,community and promotion of male involvement in sexual and reproductive health matters will improve uptake of KMC.This can be spearheadded by sexual and reproductive health, and neonatal and child health care service providers.